Seed Morphometry Reveals Two Major Groups in Spanish Grapevine Cultivars - José Javier Martín-Gómez; José Luis Rodríguez-Lorenzo; Francisco Emanuel Espinosa-Roldán; Félix Cabello Sáenz de Santamaría; Gregorio Muñoz-Organero; Ángel Tocino; Emilio Cervantes (Plants)
Seed morphological description requires quantitative methods for further comparison. Here, traditional measurements, curvature analysis, and the J-index (percentage of similarity to a geometric model) were applied to the average contours (Acs) of 271 Vitis cultivars from the Spanish collection at IMIDRA (Madrid, Spain), including 9 different Vitis species and several sylvestris seeds (i.e., those derived from plants that once grew in the wild). Acs are graphical representations of the shape in seed populations, which can be obtained either from image analysis programs or computationally opening the way to quantitative analysis. A geometric model is a geometrically defined, closed curve, used as a reference for shape quantification. Based on existing differences between the Hebén cultivar (collected in 2020 and 2024; Hebén model, for morphotype 1) and the European varieties Chenin and Gewurztraminer (Chenin model, for morphotype 2), we created two models. The comparisons were based on a J-index, resulting in four groups: Group 1 contained all seeds with values lower than 90 for both models and included all Vitis species other than V. vinifera and most sylvestris seeds; Groups 2 and 3 contained seeds with J-index values higher than 94 for the Hebén and Chenin models, respectively. Group 4 consisted of seeds not included in the other groups. Based on J-index values, differences in curvature and solidity, and PCA analysis with Fourier coefficients, this work defines two new morphotypes associated with the Hebén (Group 2) and Chenin (Group 3) models, related to Iberian and Western European varieties, respectively.